IN SILICO AND IN VIVO STUDY OF ACUTE TOXICITY OF THE SUBSTANCE OF THE MEE SERIES - Eldor Mashaev Ergashvoy ogli; Feruz Shapatov Utaganovich; Bakhtiyar Kenjaev Ismatovich (Web of Journals Publishing, 2023)
This scientific work examines forecasts and real experiments to study the acute toxicity of a substance of the MEE series. Predicted screenings were carried out using the online GUSAR program. This made it possible to reduce the number of animal deaths. Afterwards, real-life tests were carried out on outbred white mice and the results were compared. According to the final results of the study, the substances of the MEE series in the GUSAR program on rats, he predicted that the substances of the MEE series belong to 4 slightly toxic and 5 non-toxic classes of acute toxicity. In an in vivo study of the MEE-2 substance in mice, the dose was 145 mg/kg. According to the toxicity classification of substances, the substance “MEE-2” belongs to toxicity class III, moderately toxic.